Brave new world - García, Ronald Víctor ca. 20. Jh; Mazur, Dan 1959-; Tausik, David; Nimoy, Leonard 1931-2015; Gallagher, Peter 1955- (Visual Entertainment Inc., 2012)
"In a society where pleasure and conformity are all that matter, people are conditioned to live happy, promiscuous lives with the help of a mood-enhancing drug called Soma. On the fringes of the cities, savages live in reservations, free from conditioning but subject to emotions, disease and violence." -- Container